2015
DOI: 10.1523/jneurosci.4771-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Relative Unisensory Strength and Timing Predict Their Multisensory Product

Abstract: Understanding the principles by which the brain combines information from different senses provides us with insight into the computational strategies used to maximize their utility. Prior studies of the superior colliculus (SC) neuron as a model suggest that the relative timing with which sensory cues appear is an important factor in this context. Cross-modal cues that are near-simultaneous are likely to be derived from the same event, and the neural inputs they generate are integrated more strongly than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 31 publications
5
50
0
Order By: Relevance
“…For example, as shown in the present study (Experiment 1), the rat V2L cortex—a well-established area responsive to audiovisual stimuli (Toldi et al, 1986; Barth et al, 1995; Wallace et al, 2004; Hirokawa et al, 2008; Xu et al, 2014; Schormans et al, 2016)—is sensitive to differences in the timing of combined audiovisual stimuli, such that spiking activity was greatest during trials when the visual stimulus preceded the auditory by 20–40 ms (Figures 7C, 8C). These results are fairly consistent with previous studies that recorded audiovisual-evoked spiking activity in the superior colliculus (cat (Meredith and Stein, 1986, 1996; Meredith et al, 1987; Perrault et al, 2005, 2012; Stanford et al, 2005) and guinea pig (King and Palmer, 1985)) as well as multisensory cortices (cat PLLS (Allman and Meredith, 2007; Allman et al, 2008b, 2009) and cat FAES (Meredith and Allman, 2009)), and further confirm that the timing of the stimuli play a critical role in the ability of the neurons to integrate the different sensory modalities (King and Palmer, 1985; Meredith and Stein, 1986; Perrault et al, 2005; Stanford et al, 2005; Miller et al, 2015). Although the V2L cortex has been shown to play an important role in audiovisual processing, future investigations are needed in order to assess audiovisual temporal processing at the single neuron level.…”
Section: Discussionmentioning
confidence: 69%
“…For example, as shown in the present study (Experiment 1), the rat V2L cortex—a well-established area responsive to audiovisual stimuli (Toldi et al, 1986; Barth et al, 1995; Wallace et al, 2004; Hirokawa et al, 2008; Xu et al, 2014; Schormans et al, 2016)—is sensitive to differences in the timing of combined audiovisual stimuli, such that spiking activity was greatest during trials when the visual stimulus preceded the auditory by 20–40 ms (Figures 7C, 8C). These results are fairly consistent with previous studies that recorded audiovisual-evoked spiking activity in the superior colliculus (cat (Meredith and Stein, 1986, 1996; Meredith et al, 1987; Perrault et al, 2005, 2012; Stanford et al, 2005) and guinea pig (King and Palmer, 1985)) as well as multisensory cortices (cat PLLS (Allman and Meredith, 2007; Allman et al, 2008b, 2009) and cat FAES (Meredith and Allman, 2009)), and further confirm that the timing of the stimuli play a critical role in the ability of the neurons to integrate the different sensory modalities (King and Palmer, 1985; Meredith and Stein, 1986; Perrault et al, 2005; Stanford et al, 2005; Miller et al, 2015). Although the V2L cortex has been shown to play an important role in audiovisual processing, future investigations are needed in order to assess audiovisual temporal processing at the single neuron level.…”
Section: Discussionmentioning
confidence: 69%
“…Many electrophysiological studies have already shown that multisensory neurons exhibit an integrating window and SOAs of different stimuli can fall into this window and become well integrated as a single response by multisensory neurons (Miller et al . ; Felch et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is supported by multimodal neurons at some of the earliest processing stages, including the superior colliculus (SC) [79,80] and the thalamus [81], and increases in strength along cortical pathways [40]. In more detail, the SC, a midbrain structure, divides into superficial layers that are exclusively visual, and deeper layers that combine visual, auditory, and somatosensory input.…”
Section: Modality Similarities Differences and Convergencementioning
confidence: 99%
“…In more detail, the SC, a midbrain structure, divides into superficial layers that are exclusively visual, and deeper layers that combine visual, auditory, and somatosensory input. Reciprocal connections between these layers and their onward projections to the thalamus likely support early aspects of multimodal processing such as temporal binding and cross-modal enhancement (e.g., reducing a unimodal detection threshold) [79,80]. …”
Section: Modality Similarities Differences and Convergencementioning
confidence: 99%